Bibliotherapy: An Alternative Therapy in Dealing with Adolescent Problems - Soekamto, Monique Elizabeth (Faculty of Psychology, Universitas Surabaya, 2011)
Studies in psychiatry and psychology have been conducted to find alternatives of therapies to deal with the adolescent problems. One of the alternatives is bibliotherapy. Recently, the studies of bibliotherapy in Indonesia, especially in Surabaya, have been increasing. The purpose of this article is to explore the effectiveness of bibliotherapy in dealing with the adolescent problems based on theoretical review and results of some studies on bibliotherapy (Novitawati, Rahayu, & Lasmono, 2001; Sukamto, 2005; Hidayat, 2008; Patricia, 2007; Suprapto, 2009). Some studies proved that bibliotherapy was effective in reducing smoking behavior (Novitawati et al., 2001), body image dissatisfaction (Sukamto, 2005), and enhancing self-concept (Patricia, 2007), whereas the other studies(Hidayat, 2008; Suprapto, 2009) still could not prove the significant effectiveness. Beberapa penelitian di bidang psikiatri dan psikologi telah dilaksanakan untuk menemukan berbagai alternatif terapi untuk mengatasi permasalahan pada remaja. Salah satu alternatif terapi adalah bibliotherapy. Penelitian mengenai bibliotherapy di Indonesia, khususnya di Surabaya, semakin meningkat akhir-akhir ini. Tujuan dari artikel ini adalah untuk mengeksplorasi efekti- vitas bibliotherapy dalam mengatasi permasalahan pada remaja berdasarkan tinjauan teoretis dan beberapa hasil penelitian mengenai bibliotherapy (Novitawati. Rahayu, & Lasmono, 2001; Sukamto, 2005; Hidayat, 2008; Patricia, 2007; Suprapto, 2009). Beberapa penelitian membuktikan bahwa bibliotherapy efektif dalam mengurangi perilaku merokok (Novitawati et al., 2001), ketidakpuasan terhadap citra tubuh (Sukamto, 2005), dan meningkatkan konsep diri (Patricia, 2007), sedangkan penelitian yang lain (Hidayat, 2008; Suprapto, 2009) masih belum dapat menunjukkan efektivitas yang signifikan.